Wilbur Huntington Proctor papers - Proctor, Wilbur Huntington, 1849-
Diary (1864 January 1-1874 April) kept by Proctor pertaining to his military service as a musician in Company G of the 70th New York Infantry Regiment, Company K of the 86th New York Infantry Regiment, and the 14th Infantry Regiment during the U.S. Civil War and later in Idaho territory. Documents his voyage to Panama and north along the West Coast to Fort Boise, Idaho. Following his discharge from military service in 1868, Proctor describes his travels to San Francisco, Calif., Nebraska, Michigan, and Ohio; his ownership of a confectionery store; and his work as a streetcar conductor and mail carrier in New York, N.Y. Includes his description of daily life as well as genealogical data for the Proctor, Hickok, and Langdon families. Papers also include an 1891 certification of Proctor's military discharge, a 1912 certification for his military pension, and a photograph (1865 March 6) of Proctor.
Microfilm edition only of diary available
Microfilm of original diary currently held in the Beinecke Rare Book and Manuscript Library, Yale University.
Positive photocopies of original military records and photograph currently held in the Beinecke Rare Book and Manuscript Library, Yale University.
Soldier and musician.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Hickcox family; Langston family; Proctor family; United States. -- Army. -- Infantry Regiment, 14th.; United States. -- Army. -- New York Infantry Regiment, 70th (1861-1864). -- Company G; United States. -- Army. -- New York Infantry Regiment, 86th (1861-1865). -- Company K; Confectioners; Confectionery; Genealogy; Letter carriers -- New York (State) -- New York; Music and war; Postal service -- New York (State) -- New York; Railroad conductors -- New York (State) -- New York; Street-railroads -- New York (State) -- New York; Voyages and travels; California -- Description and travel; Fort Boise (Idaho); Idaho -- Description and travel; Michigan -- Description and travel; Nebraska -- Description and travel; Ohio -- Description and travel; Panama -- Description and travel; San Francisco (Calif.) -- Description and travel; New York (N.Y.) -- Social life and customs; New York (State) -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; Hickok family; Langdon family; Musicians; Soldiers